BELAJAR DARI KUNJUNGAN KE HUTAN MANGROVE DI KOTA MAKASSAR: Learning From A Visit To The Mangrove Forest In Makassar City - nurlina subair (ADPERTISI, 2022)
Writing this article aims to (i) find out what are the benefits of the existence of mangrove forests in the middle of Makassar city, (ii) who can benefit from mangrove forests. Mangrove forests play a major role in protecting the natural environment. This article uses qualitative-quantitative methods with interview, observation, and documentation studies. Data analysis used qualitative analysis. The results of the study found: (1) The benefits of the existence of a mangrove forest in the middle of the city of Makassar, namely: resisting coastal abrasion, as a community livelihood, environmental education and ecotourism. (2) Those who benefit from mangrove forests are the community, the private sector, and the government. The recommendation for this service is that mangrove forests are very important, therefore mangroves must be maintained and cultivated